2012
DOI: 10.1002/dneu.21000
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate carboxypeptidase II and folate deficiencies result in reciprocal protection against cognitive and social deficits in mice: Implications for neurodevelopmental disorders

Abstract: Interactions between genetic and environmental risk factors underlie a number of neuropsychiatric disorders, including schizophrenia (SZ) and autism (AD). Due to the complexity and multitude of the genetic and environmental factors attributed to these disorders, recent research strategies focus on elucidating the common molecular pathways through which these multiple risk factors may function. In this study, we examine the combined effects of a haplo-insufficiency of glutamate carboxypeptidase II (GCPII) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 70 publications
(86 reference statements)
1
8
1
Order By: Relevance
“…In contrast, the social interaction deficit observed in mice deficient for the GPCII, which catalyse the absorption of folates, was not affected by sex (Schaevitz et al, 2012). Finally, no sex difference was observed in COMT-/-mice that showed similar social recognition to the control groups (Babovic et al, 2008) (Table 2).…”
Section: Social Cognitioncontrasting
confidence: 61%
See 3 more Smart Citations
“…In contrast, the social interaction deficit observed in mice deficient for the GPCII, which catalyse the absorption of folates, was not affected by sex (Schaevitz et al, 2012). Finally, no sex difference was observed in COMT-/-mice that showed similar social recognition to the control groups (Babovic et al, 2008) (Table 2).…”
Section: Social Cognitioncontrasting
confidence: 61%
“…When investigating signalling pathways potentially involved in schizophrenia such as folate depletion (Schaevitz et al, 2012), a sex difference in social interaction was also observed.…”
Section: Social Cognitionmentioning
confidence: 95%
See 2 more Smart Citations
“…Betaine-induced improvements were attributed to an increase in the remethylation of homocysteine to methionine through an alternate reaction using betaine and BHMT instead of 5-MTHF and MTR. Surprisingly, folate depletion rescued social interaction impairments in GCPII +/-mice (Schaevitz et al 2012). We hypothesize that the normalization of brain folate levels (through reduced folate intake) restores methylation potential and rescues the behavior impairment in the GCPII +/-mice.…”
Section: Additional Nutraceutics From Rodent Studiesmentioning
confidence: 95%